Cognitive impairments in relapsing-remitting multiple sclerosis: a meta-analysis - Prakash, RS (2008)
There is debate in the literature regarding the magnitude, nature, and influence of cognitive impairment in individuals with relapsing-remitting multiple sclerosis (RRMS), Therefore, we conducted a meta-analysis that quantified the overall magnitude of cognitive impairment in individuals with RRMS and identified the domains of cognition and clinical/demographic variables that were moderators of the overall effect. We included 57 studies with 3891 participants that yielded a total of 755 effect sizes. Overall, there was a moderate decline in cognitive functioning in individuals with RRMS compared with healthy controls. Larger effects were observed in cognitive domains of motor functioning, mood status and memory and learning. Regarding demographic and clinical variables, age and gender were moderators of cognitive impairment in all cognitive domains, whereas neurological disability and disease duration primarily moderated performance on tasks assessing memory and learning.